2020
DOI: 10.2196/24328
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Implementation of Video Visits in Neurology During COVID-19: Mixed Methods Evaluation

Abstract: Background Telemedicine has been used for decades. Despite its many advantages, its uptake and rigorous evaluation of feasibility across neurology’s ambulatory subspecialties has been sparse. However, the COVID-19 pandemic prompted health care systems worldwide to reconsider traditional health care delivery. To safeguard health care workers and patients, many health care systems quickly transitioned to telemedicine, including across neurology subspecialties, providing a new opportunity to evaluate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(86 citation statements)
references
References 43 publications
2
84
0
Order By: Relevance
“…However, there are real limitations to a virtual examination, including the potential requirement of assistance from a caregiver, inadequate patient-home environment or space, poor lighting or discoloration with resultant poor visualization, increased time required to perform an assessment, and other technical issues [6,13,14]. In particular, the assessment of a patient's movement and motor function is limited, in part due to the need for a patient-assisted examination that can be challenging to capture on video [6,15,16]. Other aspects of a physical examination simply cannot be done via telehealth, such as auscultation of heart or lung sounds [17].…”
Section: Unintended Consequences Of Telehealthmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are real limitations to a virtual examination, including the potential requirement of assistance from a caregiver, inadequate patient-home environment or space, poor lighting or discoloration with resultant poor visualization, increased time required to perform an assessment, and other technical issues [6,13,14]. In particular, the assessment of a patient's movement and motor function is limited, in part due to the need for a patient-assisted examination that can be challenging to capture on video [6,15,16]. Other aspects of a physical examination simply cannot be done via telehealth, such as auscultation of heart or lung sounds [17].…”
Section: Unintended Consequences Of Telehealthmentioning
confidence: 99%
“…Although the world has become accustomed to online relationships, a trusting and personal connection between the patient and the health care provider, a vital aspect of health care, can be challenging to build with purely digital interaction. Multiple patient experience studies have consistently reported difficulties in communicating or connecting with providers during telehealth visits [3,6]. A desire for building an improved rapport with their providers is one of the most popular reasons why many patients prefer in-person visits [20].…”
Section: Unintended Consequences Of Telehealthmentioning
confidence: 99%
See 1 more Smart Citation
“…For technical reasons, teleradiological consultations including video-visits may be challenging for elderly CG. However, the acceptance of video-visits was found to be high [ 33 ]. Strainful transfers to medical services can be minimized and patients and CGs can communicate with their doctors, psychologist, physiotherapist, nurse, or social worker in their usual familiar environment.…”
Section: Resultsmentioning
confidence: 99%
“…Video-visit-based home rehabilitation programs have been developed. Video-visits may be less favorable for patients with severe impairments or symptom fluctuations than for patients with stable disease [ 33 ]. In summary, video consultations save time and seem altogether helpful to attenuate CB.…”
Section: Resultsmentioning
confidence: 99%